Healthcare professionals’ knowledge, attitudes and practices in thromboelastography application - Jia, Yifei; Zhu, Xiangyu; Yu, Xiaoling; Xu, Weihong; Wu, Weidong; Ye, Jianfeng; Wang, Liping (Frontiers in Medicine, 2025)
ObjectiveThis study aims to investigate the knowledge, attitudes, and practices (KAP) of healthcare professionals regarding thromboelastography (TEG).MethodsA cross-sectional study was conducted at Tongren Hospital in Shanghai from January to February 2025. Demographic data, knowledge, attitude, and practices scores, were collected and evaluated via a self-developed questionnaire.ResultsA total of 218 valid responses were included in the analysis. Of the participants, 130 (59.63%) were physicians, and 88 (40.37%) were nurses. TEG-related training had been received by 149 (68.35%) of the participants. The mean proficiency score for TEG use was 5.83 ± 2.90 (range: 0–10). The mean scores for knowledge, attitude, and practice were 8.10 ± 2.44 (range: 0–12), 30.81 ± 7.11 (range: 8–40), and 28.92 ± 8.87 (range: 8–40), respectively. Significant positive correlations were observed between knowledge and attitude (r = 0.1722, p = 0.0109) and between attitude and practice (r = 0.6945, p < 0.001). The structural equation model revealed that knowledge (β = 0.76, p < 0.001) directly influenced attitude, and attitude (β = 1.10, p < 0.001) directly influenced practice. Additionally, years of practice (β = 0.84, p = 0.003) and frequent use of TEG (β = −0.79, p = 0.024) were found to impact knowledge, which in turn affected attitude (β = 0.76, p < 0.001).ConclusionThe majority of healthcare professionals demonstrated inadequate knowledge, positive attitudes, and optimal practices regarding TEG. Enhanced training programs focused on TEG could improve proficiency and optimize its clinical application, especially for professionals with fewer years of experience.